Dampak Pendidik Bersertifikasi Terhadap Peningkatan Kinerja pada Madrasah Aliyah Negeri - Sutikno, Aris; Jasiah (Universitas Islam Negeri Mataram, Indonesia, 2025)
Certified teachers at MAN in Indonesia have a fairly large number, namely 91.37%. Certified teachers are one of the main focuses in efforts to improve the quality of education and student success. However, it is still found that more than 90% of teachers who have teacher certification have not performed optimally. The purpose of this study was to analyze the impact of teacher certification on improving the quality of education at MAN. The method used in thiqs study is the literature study method. The results obtained regarding the influence of teacher certification on teacher performance are on professional competence and ability, motivation and commitment, work environment and madrasah climate, leadership of the madrasah principal and resources and facilities. The impact of certification on teacher performance includes improving competence and professionalism, increasing motivation and self-confidence. improving the quality of learning, increasing recognition and prestige, and improving teacher welfare. The leadership of the Madrasah principal should play a role in improving teacher performance, namely by having a joint commitment to realizing the vision and mission of education, improving teacher competence, creating a positive Madrasah climate, managing resources effectively, and providing feedback and evaluation. Keywords: Teacher, Certified Educator, Performance Improvement Pendidik bersertifikasi pendidik pada MAN di Indonesia memiliki jumlah yang cukup besar yaitu 91,37%. Pendidik bersertifikasi pendidik menjadi salah satu fokus utama dalam upaya meningkatkan mutu pendidikan dan keberhasilan siswa. Namun masih ditemui 90 % lebih pendidik telah memiliki sertifikasi pendidik kinerjanya masih belum optimal. Tujuan penelitian ini adalah untuk menganalisis dampak sertifikasi pendidik terhadap peningkatan kualitas pendidikan di MAN. Metode yang digunakan dalam penelitian ini adalah metode studi pustaka. Hasil yang diperoleh mengenai pengaruh sertifikasi pendidik terhadap kinerja Pendidik adalah pada kompetensi dan kemampuan profesional, motivasi dan komitmen, lingkungan kerja dan iklim madrasah, kepemimpinan kepala Madrasah dan sumber daya serta fasilitas. Dampak sertifikasi terhadap kinerja Pendidik diantaranya meningkatkan kompetensi dan profesionalisme, meningkatkan motivasi dan kepercayaan diri. meningkatkan kualitas pembelajaran, meningkatkan pengakuan dan prestise, dan meningkatkan kesejahteraan pendidik. Seharusnya kepemimpinan kepala Madrasah berperan terhadap peningkatan kinerja pendidik yaitu dengan komitmen bersama merealisasikan visi dan misi pendidikan, meningkatkan kompetensi pendidik, menciptakan iklim madrasah positif, mengelola sumber daya efektif, dan memberikan umpan balik serta evaluasi. Kata kunci: Pendidik, Bersertifikasi Pendidik, Peningkatan Kinerja